Pengaruh penyuluhan dengan media poster terhadap peningkatan pengetahuan dan penerapan teknik pengolahan bahan makanan pada penjamah makanan di Panti Asuhan Kota Banda Aceh - Nanda Nabila; Andriani Andriani (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: Food processing workers for orphanage play an important role in processing large quantities of food. The problems that exist in the food handler staff at orphanages lack knowledge about good food processing techniques.Objectives: To find out whether there is an influence of counseling with poster media on increasing the knowledge and implementation of food processing techniques in food handlers in the orphanage of Banda Aceh.Methods: This study is descriptive analytical with an observation approach, Quasi Experiment design, with pre and post design without control. The sample is 24 food handlers. This research was conducted in June 2019. Data analysis used the Dependent T-test at a confidence level of 95%.Results: Results There was an increase in knowledge in food handlers by 9.50, namely before counseling 22.25, while after counseling the average knowledge in food handlers increased to 31.75. The increase in the application of food handlers was 8.50, which was before counseling 15.75, whereas after extension the average application for food handlers increased to 24.25. The results of the knowledge category T-test test obtained p = 0.001 (p <0.05), the application category obtained p = 0.006 (p < 0.05).Conclusion: There is a significant effect of counseling with poster media on increasing knowledge and application of food handlers in processing food ingredients at Nirmala Orphanage.